Influence of materials’ hygroscopicity in the control of relative humidity and temperature of old buildings - Gonçalves, Gonçalo Machado Monteiro Ferreira (2017)
The comfort of buildings indoor environment and materials durability are severally affected by peaks of temperature and relative humidity (RH) in interior of buildings and therefore they should be controlled and damped. The presence of people inside buildings as well as artificial illumination and all kind of equipment cause a releasing of moisture to environment, which originates an increment of its relative humidity. The occupants, artificial illumination and equipment also originate a temperature raising depending the occupants’ activity and the quantity and power of illumination and equipment. In order to reach an interior environment with values of relative humidity and temperature that ensure acceptable conditions to human health and materials longevity, it is important to install measures to control them. These measures can be active or passive if, respectively, they intend to remediate the unacceptable values of RH or temperature or if those acceptable values are achieved by installing coating materials capable of control both parameters during all seasons. If the materials are able to control temperature and relative humidity of indoor, so they contribute to improving thermal and hygroscopic inertia of buildings. Old buildings are characterized by having high thermal inertia and this means that its interior environment has a significant gap in relation to the exterior one, with regard to temperature. However, the temperature also affects relative humidity once both have an inverse relation of proportionality. This makes that it is important to damp relative humidity of old buildings indoor that would not have those values if it did not have high thermal inertia. This fact makes that be important to control relative humidity and temperature of old buildings indoor, preferably using passive measures, to preserve some very important works of art, books or documents, in case of being a museum or an archive. To control temperature and relative humidity of interior environment it is necessary to choose the best coating materials that can provide to buildings higher hygroscopic and thermal inertia. For that, it is indispensable to make correct materials characterization in order to discover their real behavior and, with base on those characteristics obtained experimentally, they could be properly chosen to be applied in buildings. In consequence of that, in the present dissertation, the materials behavior at different ranges of RH was analyzed as well as the time of exposition to those controlled environments. For that, it was chosen to make the tests of adsorption/desorption isotherm, Moisture Buffering Value (MBV), moisture permeability, thermal conductivity and response time. Additionally, the response of materials to certain interior environment was determined, by making a hygrothermal simulation in transient regime, with recourse to software Wufi Plus.